Impact of the COVID-19 Pandemic on Cancer Care and Quality of Life for Patients With Breast and Gynecologic Malignancies: A Single-Center Survey-Based Study. (February 2022) - Berger, Natalie F.; Zimmerman, Brittney S.; Seidman, Danielle; Cascetta, Krystal P.; Moshier, Erin; Nezolosky, Michelle; Trlica, Kara; Ryncarz, Alisa; Keeton, Caitlin; Tiersten, Amy
This study evaluated the mental health and cancer treatment-related impact of the first wave of the COVID-19 pandemic on patients with breast and gynecologic cancers. An 18-question survey was administered in June 2020 at a New York City-based cancer center to assess the quality of life (QOL) and overall health (OH) during both the pandemic time period from March 1, 2020, through June 30, 2020, and the pre-pandemic period (prior to March 1, 2020). Survey questions were answered on a 5-point Likert scale and a 7-point EORTC QLQ-C30 QOL scale. Differences in mean QOL and OH scores were evaluated using a paired t -test. QOL and OH were significantly worsened by the pandemic, with significant increases in anxiety, depression, and mood swings.